THE ROLE OF THE CHEMICAL INDUSTRY IN ENVIRONMENTAL POLLUTION (E Conference Zone, 2022)
The article discusses the role of polluting chemicals and chemicals produced by chemical enterprises in the development of the industry and their harmful effects on the environment and animals.